CHARACTERISTIC OVERVIEW OF DRUG RESISTANT TUBERCULOSIS IN NORTH SUMATERA PROVINCE 2024 - Sitepu, Sikap Berliana (Fakultas Kesehatan Masyarakat, Universitas Jember, 2025)
Indonesia is the second country with high insidence Tuberculosis (TBC) and Drug Resistant Tuberculosis (DR TBC) after India. Proggramatic Management Drug Resistant Tuberculosis (PMDT) is a program for MDR TBC. This research aims to investigate the characteristics of DR TBC Patients in North Sumatera Province in 2024. This research using retrospective cross sectional method with descriptive analytic. This research uses secondary data from Tuberkulosis Information System (SITB) covering the period from January – december 2024. The population are DR TBC patients with Resistant Rifampisin diagnose using Gen Expert or BD MAX amount 676 people as sampel. The result showed that majority of respondents were 69% male, age 19 -59 years in 80% with unemployed status 66%. Diagnose confirmation using Gen Expert 99,3% which 63% Resistant Rifampisin confirmed using Gen Expert (99,3%) from primary suspected criteria. Baseline diagnostic using drug resistant sensitivity test 61% and XDR test 28% with BPALM regiment (50%). Conclusion of this study that it is importance to enhance awarness and early detection or DR-TBC cases in productive age, improve access to DR-TBC treatment to enable prompt initiation, develop social and economic support strategies for DR-TBC patients, and improve the quality of data and reporting.